Açaí waste beneficing by gasification process and its employment in the treatment of synthetic and raw textile wastewater. (10th December 2019) - Pessôa, Thiago Sabino; Lima Ferreira, Letticia Emely de; da Silva, Maryne Patrícia; Pereira Neto, Luiz Martins; Nascimento, Bruna Figueiredo do; Fraga, Tiago José Marques; Jaguaribe, Emerson Freitas; Cavalcanti, Jorge Vinicius; da Motta Sobrinho, Maurício Alves
Abstract: Aiming to add value to the waste from açaí processing industry, it was used as biomass for energy production. Waste from the açai processing industry, for added value concerns, was used as biomass for energy production. The energy generated in gasification of the açaí waste was quantified at 26 kWe. In addition, the charcoal resulting from this process was activated with pure NaOH and applied as biosorbent of Methylene Blue and to reactive dyes from raw textile effluents. Specific Surface Area and Pore Distribution, Thermogravimetric analysis, Scanning Electron Microscopy, Fourier Transfer Infrared Spectroscopy and X-ray Diffraction techniques were employed to characterize the açaí biochar. Significant modifications were observed on the biochar surface morphology after its activation with NaOH. Anionic activation increased its specific surface area from 1.94 to 491.90 m 2 g −1 and led to an expressive increase in its maximum adsorption capacity for Methylene Blue from 33.73 to 93.23 mg g −1 . The equilibrium isotherm applied to fit the experimental data was the combined Langmuir Freundlich model. Kinetic experiments showed that the adsorption equilibrium was quickly reached, within 20 min. Moreover, the pseudo n order model which was the one which best fit the kinetic data and the adsorption capacity in equilibrium state (qe ) was 43.45 mg g −1 with n = 2.26. Activated açaí biochar was also investigated in the adsorption of raw textile wastewater, which exhibited a reduction of 84.62% in the effluent Biochemical Oxygen Demand. The Chemical Oxygen Demand decreased from 684 to 350 mg (O2 )∙L −1 after the combined coagulation + adsorption treatment. Graphical abstract: Image 1 Highlights: Açaí culture generates more than USD 1.5 billion per year to local communities. Açaí waste provided raw material for energy generation and sorbent production. Agroindustrial waste processing and reuse followed Circular Economy (CE) principles. Açaí charcoal possesses outstanding sorption capacity and recyclability.